2017
DOI: 10.1007/s11103-017-0603-y
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis ABI5 plays a role in regulating ROS homeostasis by activating CATALASE 1 transcription in seed germination

Abstract: It has been known that ABA INSENSITIVE 5 (ABI5) plays a vital role in regulating seed germination. In the present study, we showed that inhibition of the catalase activity with 3-amino-1,2,4-triazole (3-AT) inhibits seed germination of Col-0, abi5 mutants and ABI5-overexpression transgenic lines. Compared with Col-0, the seeds of abi5 mutants showed more sensitive to 3-AT during seed germination, while the seeds of ABI5-overexpression transgenic lines showed more insensitive. H2O2 showed the same effect on see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 56 publications
2
62
0
Order By: Relevance
“…By contrast, mitochondrial thioredoxin O1 (trxo1) mutants exhibit accelerated germination together with increased H₂O₂ levels (Ortiz-Espín et al, 2017). It was also recently shown that, in Arabidopsis thaliana, the transcription factor ABI5 regulates H 2 O 2 homeostasis in addition to its core role in ABAdependent signaling; specifically, ABI5 assists the germination process by binding to the promoter of the CATALASE 1 gene and regulating its expression and hence H 2 O 2 levels (Skubacz et al, 2016;Bi et al, 2017).…”
Section: The Role Of Ros During Germinationmentioning
confidence: 99%
“…By contrast, mitochondrial thioredoxin O1 (trxo1) mutants exhibit accelerated germination together with increased H₂O₂ levels (Ortiz-Espín et al, 2017). It was also recently shown that, in Arabidopsis thaliana, the transcription factor ABI5 regulates H 2 O 2 homeostasis in addition to its core role in ABAdependent signaling; specifically, ABI5 assists the germination process by binding to the promoter of the CATALASE 1 gene and regulating its expression and hence H 2 O 2 levels (Skubacz et al, 2016;Bi et al, 2017).…”
Section: The Role Of Ros During Germinationmentioning
confidence: 99%
“…ABI5 is a basic leucine zipper TF, playing key roles in abiotic stress response through regulating gene expression of various downstream targets [88], whereas, RAB18 is a functional protein (i.e., dehydrin), which is responsible for cellular protection under water deficit conditions [87,89]. Furthermore, a previous study demonstrated that CAT1 could be the downstream gene regulated by ABI5 [90], whereby their expression upon drought treatment were both up-regulated ( Figures 3D and 5D). Taken these results with lower water loss rates (importantly within the first h of dehydration) observed in the transgenic Arabidopsis together, it is suggested that GmRR34 enhances drought resistance of the transgenic plants in an ABA-dependent manner, at least by promoting the closure of stomata under water-deficit condition.…”
Section: Discussionmentioning
confidence: 92%
“…The expression profile of CAT was a key part of the plant defense system against oxidative stress ( Bi et al, 2017 ). In the present study, Zm CAT appeared to be regulated at the transcriptional level for detoxifying increased H 2 O 2 during cold stress conditions.…”
Section: Discussionmentioning
confidence: 99%